2017
DOI: 10.1371/journal.pone.0174912
|View full text |Cite
|
Sign up to set email alerts
|

Human microRNA-299-3p decreases invasive behavior of cancer cells by downregulation of Oct4 expression and causes apoptosis

Abstract: PurposeOct4 was reported to be one of the most important pluripotency transcription factors in the biology of stem cells including cancer stem cells, and progressed malignant cells. Here we report the investigation of gene expression control of Oct4 by selected human microRNAs and the physiological effect of Oct4 silencing in invasive cancer cells.Methods and resultsHigh throughput luciferase activity assay revealed the microRNA-299-3p to be the most effective in reducing gene expression of Oct4, which was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…These results indicate that miRNA-299 and miRNA-7706 can inhibit tumor cell proliferation. This is consistent with the finding of Göhring et al ( 17 ) that miRNA-299 can inhibit the proliferation and invasion of tumor cells. Based on those studies, we speculate that miRNA-299 and miRNA-7706 can also regulate cell proliferation and invasion in HCC.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that miRNA-299 and miRNA-7706 can inhibit tumor cell proliferation. This is consistent with the finding of Göhring et al ( 17 ) that miRNA-299 can inhibit the proliferation and invasion of tumor cells. Based on those studies, we speculate that miRNA-299 and miRNA-7706 can also regulate cell proliferation and invasion in HCC.…”
Section: Discussionsupporting
confidence: 93%
“…For example, miR-299-3p functioned as a tumor suppressor by inhibiting proliferation and invasion in human colon carcinoma (10). A similar inhibitory role of miR-299-3p was reported in breast cancer, where miR-299-3p suppressed the invasive behavior of cancer cells by targeting Oct4 (11). Additionally, Zheng et al (12) reported a role for miR-299-3p in the chemoresistance of lung cancer, as miR-299-3p promoted sensitivity to doxorubicin by directly targeting ATP-binding cassette E1.…”
Section: Introductionsupporting
confidence: 70%
“…Aberrant regulation of miRNAs is involved in controlling stemness in multiple cancers by modulating stemness-related genes [39][40][41]. MiR-34a is a tumor suppressor miRNA and is downregulated in many malignancies, for example, human liver cancer [10,11].…”
Section: Discussionmentioning
confidence: 99%